Editorial - Dossiê Artes vivas e o Antropoceno/Capitaloceno I - Gislon, Giorgio; Baumgartel, Stephan; Guzzo, Marina; Fraga, Marina; Duenha, Milene; Pires, Rafaela Blanch (Urdimento - Revista de Estudos em Artes Cênicas, 2025)
Informações sobre o conteúdo do Dossiê Temático: Artes vivas e o Antropoceno/Capitaloceno I.